Fragmentation patterns of methyloxime‐trimethylsilyl derivatives of constitutive mono‐ and disaccharide isomers analyzed by gas chromatography/field ionization mass spectrometry. (15th February 2015) - Furuhashi, Takeshi; Ishii, Keisuke; Tanaka, Kazuo; Weckwerth, Wolfram; Nakamura, Takemichi
<x xml:space="preserve">Abstract</x> RATIONALE In saccharide analysis by gas chromatography/mass spectrometry (GC/MS), electron ionization (EI) is used almost exclusively, whereas other gentler methods of ionization are rarely used. Field ionization (FI) is recognized as a GC/MS ionization method that causes fewer fragment ions, but only few studies are available on its use in saccharide analysis. METHODS To evaluate the usefulness of FI in profiling isomeric saccharides by GC/MS and to explore its potential application in metabolome analysis, we compared EI, chemical ionization (CI), and FI spectral patterns of consecutive mono‐ and disaccharides derivatized with methoxamine‐HCl and N‐methyl‐N‐(trimethylsilyl)trifluoroacetamide. RESULTS FI produced molecular ions and fragment ions characteristic of constitutive isomeric disaccharides. All of the derivatized saccharides that originally had free anomeric OH showed methyloxime‐moiety fragment ions, attributable to the cleavage between C2 and C3. Some fragment ions in FI were indicative of the position of dihexose linkages. Although EI with lowered voltage (18 V, 130 °C) produced fewer fragment ions than conventional EI (70 V, 250 °C) did, fragmentation patterns were different from those of FI. CONCLUSIONS Our data show that FI is useful for distinguishing isomeric saccharides in qualitative analyses. Copyright © 2014 John Wiley & Sons, Ltd.